Psychometric properties of the scale of alteration of the behavior in the school (SABS) - Sotelo, Lidia (2011)
The objective of this study was to analyze the psychometric properties of the Scale of Alteration of the Behavior in the School (SABS) in a sample of Peruvian children of 1º to 6º degree of elemental education, and to obtain evidences that support their use like instrument of screening for behavioural alterations (BA). One obtained an acceptable Reliability through method of internal consistency (alpha de Cronbach = 0.937), as well as evidence of internal structure of the test, factorial validity (two factors that explain 61.986% of variance) and of criterial validity. To these they say us results that the Scale of Alteration of the Behavior in the School (SABS) is an instrument valid and reliable to be used like method of valuation of behavioural alterations in students of 1.º to 6.º of primary education.